2020
DOI: 10.1177/2042753020982162
|View full text |Cite
|
Sign up to set email alerts
|

“Language not just as words”: Supporting new literacies through a design project in disadvantaged schools in Chile

Abstract: Young people are increasingly connected in a digital and globalized world, but technology-mediated interactions alone do not necessarily lead to a culture of meaningful participation and meaning making processes. Students from disadvantaged contexts are especially vulnerable to this. Drawing on the Activity-Centred Analysis and Design framework this paper discusses a case study situated in disadvantaged schools in Chile. Phase 1 of the study revealed that high school students’ literacy practices in the everyda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…The studies included in the review belonged to three categories. The first category of studies differentiated between digital cultural and social capital in the analyses (Claro et al 2012;Cortoni and Perovic 2020; Kamin and Meister 2016;Micheli 2016;Stranger-Johannessen and Norton 2017;Talaee and Noroozi 2019;Thibaut and Carvalh 2021;Vickery 2014;Zhang 2015). The second category of studies referred to a more general form of digital capital comprising cultural and social capital (Brader et al 2014;Chen 2012;Jamaludin et al 2012;Lam 2014;Mathis 2010;Noakes et al 2018;Shin and Seger 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies included in the review belonged to three categories. The first category of studies differentiated between digital cultural and social capital in the analyses (Claro et al 2012;Cortoni and Perovic 2020; Kamin and Meister 2016;Micheli 2016;Stranger-Johannessen and Norton 2017;Talaee and Noroozi 2019;Thibaut and Carvalh 2021;Vickery 2014;Zhang 2015). The second category of studies referred to a more general form of digital capital comprising cultural and social capital (Brader et al 2014;Chen 2012;Jamaludin et al 2012;Lam 2014;Mathis 2010;Noakes et al 2018;Shin and Seger 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Claro and colleagues (2012) studied 15-year-old Chilean students and found that although most students were able to complete digital tasks (e.g., searching for and organizing information), very few were able to produce digital information (e.g., developing ideas, refining, and presenting information in digital environments). Digital cultural capital valued by schools also includes digital literacies for educational purposes, and understanding of technology at the procedural (e.g., editing content online), conceptual, or safety levels (e.g., grasping the effects of their digital footprint on their lives) (Ünlüsoy et al 2010; Thibaut and Carvalh 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It continues to be important to address ethical issues, and issues of identity, agency, and privacy in education. What is more, most research on the use of technologies for learning still tends to privilege certain areas of the world (Thibaut and Carvalho 2020). The current moment offers a valuable opportunity to turn our attention to the global south and bring a more diverse voice to the conversation.…”
Section: Towards the Inclusion Of Global Local And Sustainable Views (Patricia Thibaut)mentioning
confidence: 99%
“…Por lo tanto, abordar el pensamiento crítico adquiere vital relevancia en la actualidad (Hollis, 2019). Asimismo, pese a que se asume que los estudiantes nacidos en el siglo XXI son nativos digitales (Prensky, 2001), la evidencia sugiere que ello no redunda necesariamente en favorecer procesos de aprendizaje (Selwyn, 2012;Thibaut y Carvalho, 2020).…”
Section: Introductionunclassified